The Effect of the Cranial Electrotherapy on the Muscle Motor Function in Different Operating Modes - Čupriks, Leonīds; Rudzītis, Andris; Čuprika, Aleksandra; Boičenko, Sergejs; Knipše, Gundega; Mikitčik, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the present study was to analyze the effect of cranial electrotherapy stimulation on muscle function analysis indicators. Instrumental assessment of muscle function (on a REV9000, Technogym, Italy) was performed before and after cranial electrotherapy stimulation, assessments of the muscle function was performed during knee extension maximum voluntary, isometric contraction (MVIC), angle velocity with load 45Nm isotonic contraction and maximum pick torque in isokinetic contraction on 30°/s, 200°/s and 300°/s and neuromuscular efficiency measurements. To analyze data was used Excel program Statistics 3.1. Subjects of our study were twenty healthy athletes of sport fitness. 1 minute after cranial electrotherapy application the indicators of the analysis in 80% of cases are lower than before the cranial electrotherapy. After the application of the cranial electrotherapy the inhibition phase. 10 minutes after the cranial electrotherapy application the activation phase begins. During this phase the indicators of maximum voluntary isometric contraction increase in 41% of cases, the indicators of angle velocity with load 45Nm in isotonic contraction increase in 78% of cases and maximum peak torque indicators in isokinetic contraction on 30°/s increase in 25% of cases, on 200°/s increase in 80% of cases and on 300°/s indicators increase in 25% of cases. The results obtained in the research prove that the 20 minute effect of cranial electrotherapy stimulation partly influenced by the maximum isometric muscle strength, angular velocity and peak torque. The study results could be partially useful to optimize the different modes of operation of sports.